Ruthenium-containing films deposited on ruthenium-titanium nitride films and methods for forming same
The method of depositing a ruthenium-containing film on a substrate using titanium and ruthenium precursors addresses the challenges of high resistivity and surface roughness in existing technologies, achieving improved film quality and reduced resistivity.
Patent Information
- Application Number
- JP2022543731
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-16
- Filing Date
- 2021-01-14
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-01-14
AI Technical Summary
Current methods for depositing ruthenium films on metal-containing liners face challenges such as high resistivity and surface roughness, particularly when using metal nitride liners which have higher resistivity than pure metals.
A method involving the formation of a ruthenium-containing film on a substrate, where a first film (such as ruthenium-titanium nitride) is deposited using titanium and ruthenium precursors, followed by a ruthenium-containing film formed using additional ruthenium and nitrogen-containing co-reactants, all conducted at lower temperatures using halide-free organometallic precursors.
This method achieves a ruthenium-containing film with lower resistivity and improved nucleation, resulting in smoother films with smaller particle sizes compared to existing deposition methods.
Smart Images

Figure 0007667161000008 
Figure 0007667161000009 
Figure 0007667161000010
Abstract
Description
Detailed Description of the Invention
[0001] [Technical field] The present invention relates to ruthenium-containing films deposited on ruthenium-titanium nitride (RuTiN) films and methods of forming ruthenium-containing films.
[0002] [Background technology] A variety of precursors are used to form thin films, and a variety of deposition techniques are employed. Such techniques include reactive sputtering, ion-assisted deposition, chemical vapor deposition (CVD) (also known as metalorganic CVD or MOCVD), and atomic layer deposition (also known as atomic layer epitaxy). CVD and ALD processes are increasingly being used due to their advantages of improved compositional control, high film uniformity, and effective control of doping. In addition, CVD and ALD processes provide excellent conformal step coverage in the advanced non-planar structures associated with modern microelectronic devices.
[0003] CVD is a chemical process that uses precursors to form thin films on a substrate surface. In a typical CVD process, precursors are passed over the surface of a substrate (e.g., a wafer) in a reaction chamber at low or atmospheric pressure. The precursors react and / or decompose on the substrate surface to produce a thin film of deposit. Plasma can be used to aid the precursor reaction or to improve material properties. Volatile by-products are removed by gas flow through the reaction chamber. Controlling the thickness of the deposited film can be difficult because it depends on a combination of many parameters, such as temperature, pressure, gas flow volume and uniformity, chemical depletion effects, and time.
[0004] ALD is a chemical method for the deposition of thin films. ALD is a self-limiting, continuous, and unique film growth technique based on surface reactions. This surface reaction allows precise control of thickness and allows the deposition of conformal thin films of materials provided by precursors on surface substrates of various compositions. In ALD, the precursors are separated during the reaction. The first precursor is passed over the substrate surface and produces a monolayer on the substrate surface. The excess unreacted precursor is pumped out of the reaction chamber. Then, a second precursor or co-reactant is passed over the substrate surface and reacts with the first precursor. It then forms a second monolayer of film on the first monolayer of film formed on the substrate surface. Plasma may be used to aid the reaction of the precursor or co-reactant or to improve the quality of the material. The cycle is repeated to prepare a film of the desired thickness.
[0005] Thin films, especially metal-containing thin films, have a variety of important applications, such as in nanotechnology and the manufacture of semiconductor devices. Examples of such applications include capacitor electrodes, gate electrodes, adhesive diffusion barriers, and integrated circuits.
[0006] The continuing shrinkage of the size of microelectronic components is increasing the need for improvements in thin film technology. Additionally, there is a need to deposit ruthenium as a next generation metal electrode, cap, or liner in the fabrication of logic and memory semiconductors. Additionally, metal nitride liners (e.g., titanium nitride or tungsten nitride) can be used to improve ruthenium nucleation with reduced surface roughness, but metal nitride liners have significantly higher resistivity than pure metals, which is undesirable. Thus, a process is needed for forming ruthenium-containing films on metal-containing liners, which can be carried out at lower temperatures using halide-free organometallic precursors to achieve lower resistivity films with improved ruthenium nucleation.
[0007] Summary of the Invention Thus, provided herein is a method for forming a ruthenium-containing film on a substrate. The method includes a first step of forming a first film on a surface of a substrate, and a second step of forming a ruthenium-containing film on at least a portion of the first film. The first step includes delivering a titanium precursor and a first nitrogen-containing co-reactant to the substrate, and delivering a first ruthenium precursor and a second nitrogen-containing co-reactant to the substrate to form a first film. The second step includes delivering a second ruthenium precursor and a third co-reactant to the substrate and / or the first film.
[0008] In another embodiment, a ruthenium-containing film is provided. The ruthenium-containing film includes a first film deposited on a surface of a substrate, and the ruthenium-containing film deposited on at least a portion of the first film. The first film includes a first reaction product of a titanium precursor and a first nitrogen-containing co-reactant, and a second reaction product of a first ruthenium precursor and a second nitrogen-containing co-reactant. The ruthenium-containing film includes a third reaction product of a second ruthenium precursor and a third co-reactant.
[0009] Other embodiments, incorporating certain aspects of the embodiments summarized above, will become apparent from the following detailed description.
[0010] BRIEF DESCRIPTION OF THE DRAWINGS FIG. 1A is a graphical representation of the growth rate (nm / cycle) of as-deposited ruthenium-titanium nitride (RuTiN) films versus Ti / Ru cycle ratio for RuTiN films grown on three substrates (Al2O3, SiO2, and WCN) according to Example 1.
[0011] FIG. 1B is a graphical representation of the growth rate (nm / cycle) of annealed RuTiN films versus Ti / Ru cycle ratio for annealed RuTiN films grown on three substrates (Al2O3, SiO2, and WCN) according to Example 1.
[0012] FIG. 1C is a graphical representation comparing the growth rate (nm / cycle) versus Ti / Ru cycle ratio for as-deposited RuTiN films grown on SiO2 and annealed RuTiN films grown on SiO2 from FIGS. 1A and 1B.
[0013] FIG. 2A is a graphical representation comparing resistivity (μΩcm) versus Ti / Ru cycling ratio for as-deposited RuTiN films grown on Al2O3 (“as-deposited”) and annealed RuTiN films grown on Al2O3.
[0014] FIG. 2B is a graphical representation comparing resistivity (μΩcm) versus Ti / Ru cycling ratio for as-deposited RuTiN films grown on SiO (“as-deposited”) and annealed RuTiN films grown on SiO.
[0015] FIG. 2C is a graphical representation comparing resistivity (μΩcm) versus Ti / Ru cycling ratio for as-deposited RuTiN films grown on WCN (“as-deposited”) and annealed RuTiN films grown on WCN.
[0016] FIG. 3A is a graphical representation of the XPS depth profile of an annealed RuTiN film formed on SiO 2 with a Ti / Ru cycling ratio of 1:2.
[0017] FIG. 4A is a graphical representation comparing resistivity (μΩcm) versus Ti / Ru cycle ratio for as-deposited thick RuTiN films (13-20 nm) grown on Al2O3, SiO2, and WCN according to Example 4.
[0018] FIG. 4B is a graphical representation comparing resistivity (μΩcm) versus Ti / Ru cycle ratio for as-deposited thin RuTiN films (2-5 nm) grown on Al2O3, SiO2, and WCN according to Example 4.
[0019] FIG. 5A is a graphical representation comparing resistivity (μΩcm) versus Ti / Ru cycling ratio for annealed thick RuTiN films (13-20 nm) grown on Al 2 O 3 , SiO 2 , and WCN according to Example 5.
[0020] FIG. 5B is a graphical representation comparing resistivity (μΩcm) versus Ti / Ru cycle ratio for annealed thin RuTiN films (2-5 nm) grown on Al 2 O 3 , SiO 2 , and WCN according to Example 5.
[0021] 6A-6E are scanning electron microscope (SEM) images of the surfaces of annealed RuTiN films formed on SiO 2 with Ti / Ru cycle ratios of 1:4, 1:3, 1:2, 2:3, and 1:1, respectively.
[0022] Figures 7A-7C are SEM images of the surface of annealed RuTiN films formed on 4 nm Al2O3 / 100 nm SiO2 with Ti / Ru cycling ratios of 1:3, 1:2, and 1:1, respectively. Figure 7D is an SEM image of the surface of a RuTiN film annealed with a Ti / Ru cycling ratio of 1:1 on 25 nm Al2O3 / native SiO2 (denoted as "thick Al2O3" or "Al2O3_thick on Si").
[0023] FIG. 7E is a graphical representation of AFM roughness (nm) versus Ti / Ru cycling ratio for annealed films formed on various substrates.
[0024] 8A-8E are SEM images of the surfaces of as-deposited Ru films formed directly on 100 nm SiO2 substrates (no liner) and Ru films formed in-situ on as-deposited RuTiN film liners on 100 nm SiO2 or 4 nm Al2O3 / 100 nm SiO2.
[0025] Figure 9A is a graphical representation of AFM roughness (nm) versus Ru thickness (nm) measured by X-ray fluorescence (XRF) for Ru films formed by ALD on liners (RuTiN, TiN, TiN_OEM, and WCN) on 100 nm SiO2, and also directly on 100 nm SiO2 without the use of a liner.
[0026] Figure 9B is a graphical representation of AFM roughness (nm) versus Ru thickness (nm) measured by X-ray fluorescence (XRF) for Ru films formed by ALD on liners on 4 nm Al2O3 / 100 nm SiO2 (RuTiN, TiN, and TiN on 25 nm Al2O3 / Si with pure SiO2 (Al2O3 / Si)) and also directly on 4 nm Al2O3 / 100 nm SiO2 without the use of a liner.
[0027] 10A-10E are SEM images of the surface of RuTiN films formed on 100 nm SiO2 or 4 nm Al2O3 / 100 nm SiO2.
[0028] FIG. 10F is a graphical representation of AFM roughness (nm) versus estimated RuTiN liner thickness (nm) for annealed RuTiN films formed on 100 nm SiO 2 or 4 nm Al 2 O 3 / 100 nm SiO 2 .
[0029] 11A and 11B are cross-sectional SEM images of a hole structure coated with 6.5 nm of Ru on top of a 3 nm in-place RuTiN liner (1:2 cycle ratio) deposited at 225°C.
[0030] Detailed Description Before describing some example embodiments of the present technology, it should be understood that the technology is not limited to the details of construction or process steps set forth in the following description as the technology is capable of other embodiments and of being practiced or carried out in various ways.
[0031] The inventors have discovered a two-step process for improving ruthenium deposition and the films formed therefrom. The process may include depositing a first film or liner (e.g., RuTiN-containing film) on a substrate using a titanium precursor as described herein, a first nitrogen-containing co-reactant as described herein, a first ruthenium precursor as described herein, and a second nitrogen-containing co-reactant. A ruthenium-containing film can be formed on the first film by delivering a second ruthenium precursor as described herein and a third co-reactant. Advantageously, the process described herein can be carried out at lower temperatures (e.g., 350° C. or less) and using halide-free precursors. The first film formed has a lower resistivity compared to other metal nitride liners as a result of doping the first film with ruthenium. It has been discovered that the deposition processes described herein provide smoother ruthenium films with smaller grain sizes and lower resistivity as compared to current deposition methods for forming ruthenium thin films (including current ALD processes for forming ruthenium thin films and ALD processes that use metal nitride liners).
[0032] (definition) For purposes of this invention and the claims, the numbering scheme for the Periodic Table Groups follows the IUPAC Periodic Table of the Elements.
[0033] As used herein, the term "and / or" in phrases such as "A and / or B" is intended to include "A and B," "A or B," "A," and "B."
[0034] The terms "substituent," "radical," "group," and "moiety" may be used interchangeably.
[0035] As used herein, the terms "metal-containing complex" (or more simply "complex") and "precursor" are used interchangeably to refer to a metal-containing molecule or compound that can be used to prepare a metal-containing film by a vapor deposition process such as, for example, ALD or CVD. The metal-containing complex may be deposited, adsorbed, decomposed, delivered, and / or passed onto a substrate or surface thereof to form a metal-containing film.
[0036] As used herein, the term "metal-containing film" includes not only elemental metal films, as more fully defined below, but also films that include a metal along with one or more elements, such as metal nitride films, metal silicide films, metal carbide films, etc. As used herein, the terms "elemental metal film" and "pure metal film" are used interchangeably to refer to a film that consists of a pure metal or consists essentially of a pure metal. For example, an elemental metal film may include 100% pure metal, or an elemental metal film may include at least about 70%, at least about 80%, at least about 90%, at least about 95%, at least about 96%, at least about 97%, at least about 98%, at least about 99%, at least about 99.9%, or at least about 99.99% pure metal along with one or more impurities. Unless the context indicates otherwise, the term "metal film" shall be interpreted to mean an elemental metal film.
[0037] As used herein, the term "vapor deposition process" is used to denote any type of vapor deposition technique, including, but not limited to, CVD and ALD. In various embodiments, CVD may take the form of conventional (i.e., continuous flow) CVD, liquid injection CVD, plasma-enhanced CVD, or photo-assisted CVD. CVD may take the form of pulsed techniques (i.e., pulsed CVD). ALD is used to form metal-containing films by vaporizing and / or passing at least one metal complex disclosed herein over a substrate surface. For conventional ALD processes, see, for example, George SM, et al. J. Phys. Chem., 1996, 100, 13121-13131. In other embodiments, ALD may take the form of conventional (i.e., pulsed injection) ALD, liquid injection ALD, photo-assisted ALD, plasma-assisted ALD, or plasma-enhanced ALD. The term "vapor deposition process" may include various vapor deposition techniques as described in Chemical Vapour Deposition: Precursors, Processes, and Applications; Jones, AC; Hitchman, ML, Eds. The Royal Society of Chemistry: Cambridge, 2009; Chapter 1, pp 1-36.
[0038] The term "alkyl" refers to a saturated hydrocarbon chain of 1 to about 8 carbon atoms in length, such as, but not limited to, methyl, ethyl, propyl, and butyl. Alkyl groups may be straight or branched chain. For example, as used herein, propyl includes both n-propyl and isopropyl, and butyl includes n-butyl, sec-butyl, isobutyl, and tert-butyl. Additionally, as used herein, "Me" refers to methyl and "Et" refers to ethyl.
[0039] (Ruthenium-containing film and method for forming same) As described above, ruthenium-containing films and methods of forming ruthenium-containing films are provided herein. The ruthenium-containing film can include a first film (or liner) disposed on a surface of a substrate and a ruthenium-containing film disposed on at least a portion of the first film. The first film can include a first reaction product of a titanium precursor and a first nitrogen-containing co-reactant, and a second reaction product of a first ruthenium precursor and a second nitrogen-containing co-reactant. In any embodiment, the first film can include ruthenium-titanium nitride (RuTiN). In any embodiment, the first film can include a first layer adjacent to the surface of the substrate. The first layer includes the first reaction product. The first layer and / or the first reaction product can also optionally include a dissociated portion of the titanium precursor, a dissociated portion of the first nitrogen-containing co-reactant, or a combination thereof. In some embodiments, the first film can include a second layer adjacent to the first layer. The second layer includes the second reaction product. The second layer and / or the second reaction product may also optionally include a dissociated portion of the first ruthenium precursor, a dissociated portion of the second nitrogen-containing co-reactant, or a combination thereof. Additionally or alternatively, the first film may include ruthenium therein as a dopant. For example, the first film may include a first reaction product (e.g., present as a first layer) and a second reaction product (e.g., present as a second layer). In this case, the first layer, the second layer, or both layers are doped with ruthenium. A plasma may be used to enhance the reaction of the precursor or co-reactant, or to improve the quality of the film.
[0040] In any embodiment, the ruthenium-containing film can include a third reaction product of the second ruthenium precursor and a third co-reactant, and, optionally, a dissociated portion of the second ruthenium precursor, a dissociated portion of the third co-reactant, or a combination thereof. It is contemplated herein that the first film, first layer, second layer, and ruthenium-containing film can each be a continuous layer or a discontinuous layer.
[0041] The method of preparing the ruthenium-containing film may include a first step and a second step. In any embodiment, the first step may include forming a first film (or liner) on the surface of the substrate by delivering a titanium precursor and a first nitrogen-containing co-reactant to the substrate. The first step further includes delivering a first ruthenium precursor and a second nitrogen-containing co-reactant to the substrate. In various aspects, the first film may include the first reaction product and the second reaction product. In further aspects, the first film may include the first layer, the second layer, or a combination thereof. Additionally or alternatively, the first film may include ruthenium therein as a dopant.
[0042] In an optional embodiment, the second step can include delivering a second ruthenium precursor and a third co-reactant to the substrate to form a ruthenium-containing film on at least a portion of the first film. The ruthenium-containing film can include the third reaction product described above.
[0043] In any embodiment, the first step, the second step, or a combination thereof may include the use of plasma. The use of plasma may enhance the reaction of, for example, one or more of the titanium precursor, the first ruthenium precursor, the second ruthenium precursor, the first nitrogen-containing co-reactant, the second nitrogen-containing co-reactant, and the third co-reactant. Additionally or alternatively, the use of plasma may improve the quality of the film.
[0044] In any embodiment, the structure of the titanium precursor corresponds to Formula I: [R 1 R 2 N]4Ti (Formula I) In the formula, R 1 and R 2 are each independently C1-C6 alkyl. In some embodiments, R 1 and R 2are each independently C1-C4 alkyl or C1-C2 alkyl. Examples of suitable titanium precursors include, but are not limited to, tetrakis(dimethylamido)titanium (also known as tetrakis(dimethylamino)titanium) (TDMAT), tetrakis(ethylmethylamido)titanium (also known as tetrakis(ethylmethylamino)titanium), and tetrakis(diethylamido)titanium (also known as tetrakis(diethylamino)titanium).
[0045] In any embodiment, the first ruthenium precursor is (η 4 -2,3-Dimethylbuta-1,3-diene)tricarbonylruthenium ((DMBD)Ru(CO)3), (η 4 -Buta-1,3-diene)tricarbonylruthenium ((BD)Ru(CO)3), (1,3-cyclohexadienyl)tricarbonylruthenium (((CHD)Ru(CO)3), (η 4 -2-Methylbuta-1,3-diene)tricarbonylruthenium, or triruthenium dodecacarbonyl Ru3(CO) 12 Includes.
[0046] In any embodiment, the second ruthenium precursor is (η 4 -2,3-Dimethylbuta-1,3-diene)tricarbonylruthenium ((DMBD)Ru(CO)3), (η 4 -Buta-1,3-diene)tricarbonylruthenium ((BD)Ru(CO)3), (1,3-cyclohexadienyl)tricarbonylruthenium (((CHD)Ru(CO)3), (η 4 -2-Methylbuta-1,3-diene)tricarbonylruthenium, triruthenium dodecacarbonyl Ru3(CO) 12, or other Ru(0) or Ru(II) ruthenium precursors such as (ethylbenzyl)(1-ethyl-1,4-cyclohexadienyl)ruthenium(0) (Ru(EtBz)(EtCHD)), bis(ethylcyclopentadienylruthenium(II) (Ru(EtCp)2), (cyclopentadienyl)(ethyl)biscarbonylruthenium(0) (Cp(Et)Ru(CO)2), or (N,N'-diisopropylacetamidinato)biscarbonylruthenium(II) ((amidinato)Ru(CO)2). In any embodiment, the first ruthenium precursor and the second ruthenium precursor can be the same.
[0047] In some embodiments, the titanium precursor, the first ruthenium precursor, the second ruthenium precursor, or a combination thereof may be dissolved in a suitable solvent, such as a hydrocarbon solvent or an amine solvent, to facilitate the deposition process. Suitable hydrocarbon solvents include, but are not limited to, aliphatic hydrocarbons (e.g., hexane, heptane, and nonane); aromatic hydrocarbons (e.g., toluene and xylene); and aliphatic and cyclic ethers (e.g., diglyme, triglyme, and tetraglyme). Examples of suitable amine solvents include, but are not limited to, octylamine and N,N-dimethyldodecylamine. For example, the titanium precursor, the first ruthenium precursor, the second ruthenium precursor, or a combination may be dissolved in toluene to obtain a solution with a concentration of about 0.05M to about 1M.
[0048] In an alternative embodiment, the titanium precursor, the first ruthenium precursor, the second ruthenium precursor, or a combination may be delivered to the substrate surface "neat" (undiluted by a carrier gas).
[0049] Thus, the precursors disclosed herein utilized in these methods may be liquid, solid, or gaseous. Typically, the ruthenium precursor is a liquid or solid at ambient temperature that has sufficient vapor pressure to allow consistent transport of the vapor to the processing chamber.
[0050] The first nitrogen-containing co-reactant and the second nitrogen-containing co-reactant can each independently be selected from the group consisting of NH3, alkylamines, hydrazines, alkylhydrazines, and combinations thereof. In various embodiments, the alkylhydrazine can be a C1-C8 alkylhydrazine, a C1-C4 alkylhydrazine, or a C1-C2 alkylhydrazine. For example, the alkylhydrazine can be methylhydrazine, ethylhydrazine, propylhydrazine, or butylhydrazine (including tertiary butylhydrazine).
[0051] In any embodiment, the third co-reactant can be selected from the group consisting of hydrogen, hydrogen plasma, nitrogen plasma, ammonia plasma, oxygen, air, water, H2O2, ozone, i-PrOH, t-BuOH, NO, ammonia, alkylamines, hydrazine, borane, silane, ozone, and combinations of any two or more thereof. In some embodiments, the third co-reactant can be a third nitrogen-containing co-reactant (e.g., selected from the group consisting of NH3, alkylamines, hydrazine, alkylhydrazine, and combinations thereof).
[0052] In various embodiments, the substrate surface may comprise a metal, a dielectric material, a metal oxide material, or a combination thereof. The dielectric material may be a low-κ or high-κ dielectric. Examples of suitable dielectric materials include, but are not limited to, SiO2, SiN, and combinations thereof. Examples of suitable metal oxide materials include, but are not limited to, HfO2, ZrO2, SiO2, Al2O3, TiO2, and combinations thereof. Other suitable substrate materials include, but are not limited to, silicon, crystalline silicon, Si(100), Si(111), glass, strained silicon, silicon-on-insulator (SOI), doped silicon or silicon oxide (e.g., silicon oxide doped with carbon), germanium, gallium arsenide, tantalum, tantalum nitride, aluminum, copper, ruthenium, titanium, titanium nitride, tungsten, tungsten nitride, tungsten carbonitride (WCN), and any number of other substrates commonly encountered in nanoscale device fabrication processes (e.g., semiconductor fabrication processes). As will be appreciated by those skilled in the art, the substrate may be exposed to a pretreatment process to polish, etch, reduce, oxidize, hydroxylate, anneal, and / or bake the substrate surface. In one or more embodiments, the substrate surface comprises a hydrogen-terminated surface.
[0053] The methods provided herein encompass various types of ALD and / or CVD processes, including, but not limited to, continuous or pulsed injection processes, liquid injection processes, photo-assisted processes, plasma-assisted processes, and plasma-enhanced processes, etc. For example, the first and second steps can be ALD or CVD processes.
[0054] In some embodiments, conventional CVD or pulsed CVD is used to vaporize and / or pass a titanium precursor, a first ruthenium precursor, and / or a second ruthenium precursor (all as disclosed herein) over a substrate surface to form the first film described herein and / or the ruthenium-containing film described herein. For conventional CVD processes, see, for example, Smith, Donald (1995). Thin-Film Deposition: Principles and Practice. McGraw-Hill.
[0055] In other embodiments, photo-assisted CVD is used to form a first film described herein and / or a ruthenium-containing film described herein by vaporizing and / or passing a titanium precursor, a first ruthenium precursor, and / or a second ruthenium precursor (all as disclosed herein) over a substrate surface.
[0056] In some embodiments, conventional (i.e., pulsed injection) ALD is used to form the first film described herein and / or the ruthenium-containing film described herein by vaporizing and / or passing a titanium precursor, a first ruthenium precursor, and / or a second ruthenium precursor (all as disclosed herein) over a substrate surface. For conventional ALD processes, see, for example, George SM, et al. J. Phys. Chem., 1996, 100, 13121-13131.
[0057] In another embodiment, liquid injection ALD is used to form the first film described herein and / or the ruthenium-containing film described herein by vaporizing and / or passing a titanium precursor, a first ruthenium precursor, and / or a second ruthenium precursor (all as disclosed herein) over a substrate surface. The precursors are delivered to the reaction chamber by direct liquid injection as opposed to vapor suction through a bubbler. For liquid injection ALD processes, see, for example, Potter RJ, et al., Chem. Vap. Deposition, 2005, 11(3), 159-169.
[0058] In other embodiments, photo-assisted ALD is used to form the first film described herein and / or the ruthenium-containing film described herein by vaporizing and / or passing at least one precursor disclosed herein over a substrate surface. For photo-assisted ALD processes, see, for example, U.S. Patent No. 4,581,249.
[0059] In other embodiments, plasma-assisted or plasma-enhanced ALD is used to form a first film described herein and / or a ruthenium-containing film described herein by vaporizing and / or passing a titanium precursor, a first ruthenium precursor, and / or a second ruthenium precursor (all as disclosed herein) over a substrate surface.
[0060] In further embodiments, the first step (e.g., during an ALD process) can include a super cycle that includes a titanium cycle and a ruthenium cycle. The titanium cycle can include delivering a titanium precursor, a first nitrogen-containing co-reactant, and a purge gas to the substrate. For example, the titanium precursor can be pulsed for 0.01-1 seconds, followed by delivering a purge gas for 5-15 seconds, followed by pulsing the first nitrogen-containing co-reactant for 0.001-1 seconds, followed by delivering a purge gas for 5-15 seconds. The ruthenium cycle can include delivering a first ruthenium precursor, a second nitrogen-containing co-reactant, and a purge gas to the substrate. For example, the first ruthenium precursor can be pulsed for 0.01-1 seconds, followed by delivering a purge gas for 5-15 seconds, followed by pulsing the second nitrogen-containing co-reactant for 0.001-1 seconds, followed by delivering a purge gas for 5-15 seconds.
[0061] The super cycle can include "m" titanium cycles followed by "n" ruthenium cycles. m and n can range from 1 to 100 cycles, 1 to 75 cycles, 1 to 50 cycles, 1 to 25 cycles, 1 to 10 cycles, or 1 to 5 cycles, respectively. The ratio of titanium cycles to ruthenium cycles can range from 1:1 to 2:12 or 1:1 to 2:10. Depending on the ratio of titanium cycles to ruthenium cycles, the Ti:Ru concentration ratio of the first film can be from about 1:10 to about 10:1.
[0062] In some embodiments, the supercycle can include one titanium cycle followed by 1-50 ruthenium cycles, 1-25 ruthenium cycles, or 1-10 ruthenium cycles. Alternatively, the supercycle can include two titanium cycles followed by three ruthenium cycles. The total number of supercycles can range from 1-100, 1-75, 1-50, 1-25, 1-10, or 1-5.
[0063] In various embodiments, the second step can include an additional ruthenium cycle including delivering a second ruthenium precursor, a third co-reactant, and a purge gas to the substrate. For example, the third ruthenium precursor can be pulsed for 0.01-1 seconds, followed by delivery of a purge gas for 5-15 seconds, followed by delivery of a third co-reactant for 0.001-1 seconds, followed by delivery of a purge gas for 5-15 seconds. Any suitable purge gas can be used in the first and second steps, such as nitrogen, hydrogen, and noble gases (e.g., helium, neon, argon, krypton, xenon, etc.).
[0064] The reaction time, temperature and pressure of the methods described herein are selected to produce a first film and a ruthenium-containing film on the surface of the substrate. The reaction conditions will be selected based on the properties of the titanium precursor, the first ruthenium precursor, and the second ruthenium precursor. The deposition can be carried out at atmospheric pressure, but is more commonly carried out at reduced pressure. The vapor pressures of the titanium precursor, the first ruthenium precursor, and the second ruthenium precursor must be high enough to be practical in such applications. The substrate temperature must be low enough to keep the bonds between the metal atoms at the surface intact and prevent thermal decomposition of the gaseous reactants. However, the substrate temperature must also be high enough to keep the source materials (i.e., reactants) in the gas phase and provide sufficient activation energy for the surface reactions. The appropriate temperature depends on a variety of parameters, including the particular titanium precursor, the first ruthenium precursor, and the second ruthenium precursor used, as well as the pressure. In some embodiments, the first step, the second step, or both steps may be carried out at a temperature of about 350° C. or less, about 300° C. or less, about 275° C. or less, about 250° C. or less, about 225° C. or less, or about 200° C. or less, or from about 150° C. to about 350° C., preferably from about 200° C. to about 250° C. The above temperatures are understood to represent the substrate temperature. In any embodiment, the first step, the second step, or both steps may be carried out in an inert atmosphere (e.g., an argon atmosphere).
[0065] The properties of the specific titanium precursor, first ruthenium precursor, and second ruthenium precursor for use in the deposition methods disclosed herein can be evaluated using methods known in the art, allowing the selection of appropriate temperatures and pressures for the reaction. In general, low molecular weight and the presence of functional groups that increase the rotational entropy of the ligand sphere result in melting points that produce liquids at typical delivery temperatures and increased vapor pressures.
[0066] The titanium precursor, the first ruthenium precursor, and the second ruthenium precursor for use in the deposition method will have all of the requirements for sufficient vapor pressure, sufficient thermal stability at the temperature of the selected substrate, and sufficient reactivity to cause a reaction on the surface of the substrate without introducing undesirable impurities into the thin film. Sufficient vapor pressure ensures that the molecules of the source compound are present on the surface of the substrate in sufficient concentration to allow a complete self-saturating reaction. Sufficient thermal stability ensures that the source compound does not undergo thermal decomposition that would produce impurities in the thin film.
[0067] Examples of ALD growth conditions for the titanium precursor, first ruthenium precursor, and second ruthenium precursor disclosed herein include, but are not limited to, the following: (1) Substrate temperature: 200 to 300°C (2) Evaporator temperature (metal precursor temperature): 20 to 70°C (3) Reactor pressure: 0.01 to 10 Torr (4) Argon or nitrogen carrier gas flow rate: 0 to 100 sccm (5) Reactive gas (co-reactant) pulse time: 0.01-1 sec. Pulse sequence (metal complex / purge / reactive gas / purge): will vary depending on chamber size. (6) Number of cycles: will vary depending on desired film thickness.
[0068] In further embodiments, the methods described herein may be performed under conditions that provide conformal growth, for example for the first film. As used herein, the term "conformal growth" refers to a deposition process in which a film is deposited at substantially the same thickness along one or more of the bottom, sides, top corners, and outside of a feature. "Conformal growth" is also intended to encompass some variation in film thickness, for example, a film may be thicker near the outside and / or top or top of a feature compared to the bottom or bottom of the feature.
[0069] A conformal growth cycle may include carrying out the above super cycle under conformal conditions where conformal growth occurs. Conformal conditions include, but are not limited to, temperature (e.g., of the substrate, titanium precursor, first ruthenium precursor, second ruthenium precursor, purge gas, co-reactant, etc.), pressure (e.g., during delivery of the titanium precursor, first ruthenium precursor, second ruthenium precursor, purge gas, co-reactant, etc.), amount of titanium precursor, first ruthenium precursor, second ruthenium precursor and / or co-reactant delivered, and / or length of purge time and / or amount of purge gas delivered. In various embodiments, the substrate may include one or more features where conformal growth may occur.
[0070] In various aspects, the features may be holes, trenches, contacts, dual damascene, etc. The features may have a non-uniform width, also known as "recessed features," or the features may have a substantially uniform width.
[0071] In one or more embodiments, the first film and / or the ruthenium-containing film grown according to the methods described herein may be substantially free of seams that are voids and / or cavities.
[0072] In any embodiment, the method described herein can further include annealing the as-deposited first film, the as-deposited ruthenium-containing film, or both films at a higher temperature. In other words, the annealing can be performed after the last cycle for forming the first film and / or the last cycle for forming the ruthenium-containing film. The annealing step helps to provide a quality ruthenium film with less impurities and less resistivity.
[0073] Thus, in some embodiments, the as-deposited first film, the as-deposited ruthenium-containing film, or both films may be annealed under vacuum or in the presence of an inert gas such as Ar or N2, or a reducing agent such as H2 or NH3, or a combination thereof, such as, for example, 5% H2 in Ar or 5% H2 in Ar. Without being bound by theory, the annealing step may remove carbon, oxygen, and / or nitrogen incorporated by densification at high temperatures to reduce resistivity and further improve film quality. Annealing may be performed at temperatures of about 300° C. or higher, about 400° C. or higher, or about 500° C.; about 300° C. to about 500° C., or about 400° C. to about 500° C.
[0074] The first films and ruthenium-containing films formed from the methods described herein can have lower resistivities. In some embodiments, the resistivity of the first film can be about 20 μΩcm or more, about 40 μΩcm or more, about 60 μΩcm or more, about 80 μΩcm or more, about 100 μΩcm or more, about 250 μΩcm or more, about 500 μΩcm or more, about 1000 μΩcm or more, about 1500 μΩcm or more, about 2000 μΩcm or more, about 2500 μΩcm or more, or about 3000 μΩcm or more; or about 20 μΩcm to about 3000 μΩcm, about 100 μΩcm to about 3000 μΩcm, about 500 μΩcm to about 3000 μΩcm, about 100 μΩcm to about 2000 μΩcm, about 100 μΩcm to about 1000 μΩcm, or about 100 μΩcm to about 500 μΩcm. In some embodiments, the resistivity of the first film after annealing can be reduced to, for example, about 10 μΩcm or more, about 20 μΩcm or more, about 50 μΩcm or more, about 100 μΩcm or more, about 250 μΩcm or more, or about 500 μΩcm or more; or to a resistivity of about 10 μΩcm to about 500 μΩcm, or about 20 μΩcm to about 250 μΩcm.
[0075] The above resistivity measurements may be achieved in a first film prepared by the methods described herein having a thickness, as measured by XRF, of about 1 nm to about 20 nm, about 1 nm to about 15 nm, about 2 nm to about 15 nm, about 2 nm to about 10 nm, or about 1 nm to about 5 nm.
[0076] Advantageously, the roughness of the film formed from the process described herein is reduced. For example, the roughness of the first film measured by AFM can be about 2 nm or less, about 1.8 nm or less, about 1.6 nm or less, about 1.4 nm or less, about 1.2 nm or less, or about 1 nm or less; or about 1 nm to about 2 nm, about 1 nm to about 1.8 nm, about 1 nm to about 1.6 nm, or about 1 nm to about 1.4 nm, measured by AFM. Additionally or alternatively, the roughness of the ruthenium-containing film measured by AFM can be about 1.0 nm or less, about 0.8 nm or less, about 0.65 nm or less, about 0.4 nm or less, or about 0.2 nm or less; or about 0.2 nm to about 1.0 nm, about 0.2 nm to about 0.8 nm, or about 0.2 nm to about 0.65 nm, measured by AFM.
[0077] (Application) The films formed from the processes described herein are useful for memory and / or logic applications such as dynamic random access memory (DRAM), complementary metal oxide semiconductor (CMOS), and 3D NAND, 3D crosspoint, and ReRAM.
[0078] Throughout this specification, reference to "one embodiment," "a particular embodiment," "one or more embodiments," or "an embodiment" means that a particular feature, structure, material, or characteristic described in connection with this embodiment is included in at least one embodiment of the technology. Thus, the appearances of phrases such as "in one or more embodiments," "in a particular embodiment," "in one embodiment," or "in an embodiment" in various places throughout this specification do not necessarily refer to the same embodiment of the technology. Furthermore, particular features, structures, materials, or characteristics may be combined in any suitable manner in one or more embodiments.
[0079] Although the present technology has been described with reference to specific embodiments, it should be understood that these embodiments merely illustrate the principles and applications of the present technology. It will be apparent to those skilled in the art that various modifications and variations can be made to the methods and devices of the present technology without departing from the spirit and scope of the present technology. Therefore, the present technology is intended to include modifications and variations that fall within the scope of the appended claims and their equivalents. Thus, the present technology has been generally described, but will be more readily understood by referring to the following examples, which are provided for illustrative purposes and are not intended to be limiting.
[0080] [Example] In the following examples, (DMBD)Ru(CO)3 (also referred to as RuDMBD) and TDMAT were used as precursors. Methods for preparing (DMBD)Ru(CO)3 are known in the art. See, for example, U.S. Patent Application Publication No. 2011 / 0165780, the entire contents of which are incorporated herein by reference.
[0081] Unless otherwise stated, ruthenium-titanium nitride (RuTiN) films were deposited in an ALD process using (DMBD)Ru(CO)3 and TDMAT in a CN1 ALD / CVD reactor under the following conditions: (i) In an argon atmosphere, at a temperature of 225°C and a pressure of 0.94 Torr; (ii) TDMAT was delivered to the substrate at 50° C. in a titanium cycle as follows: 1 s pulse TDMAT (bubbler), 10 s purge with argon, 0.075 s hydrazine co-reactant pulse, and 10 s purge with argon.
[0082] (iii) (DMBD)Ru(CO) was delivered to the substrate at 40 °C in a ruthenium cycle as follows: 1 s pulse (DMBD)Ru(CO) (bubbler), 10 s purge with argon, 0.075 s hydrazine coreactant pulse, and 10 s purge with argon.
[0083] (iv) RuTiN films were deposited using a supercycle comprising one titanium cycle followed by "n" ruthenium cycles (except when two titanium cycles followed by three ruthenium cycles were performed).
[0084] (v) Ti / Ru cycle ratio=1 / n, indicating the relative Ti concentration in the RuTiN film.
[0085] (vi) Where annealing of the RuTiN films occurred, the films were either annealed in the reactor immediately after deposition or exposed to air for a short period of time (e.g., 2 min or less) and then reloaded into the reactor under vacuum for annealing.
[0086] (vii) The resistivity of the RuTiN films was based on ellipsometer thickness unless otherwise stated.
[0087] [Example 1] Average growth rate: Dependence on Ti / Ru cycle ratio RuTiN films with thicknesses of 13–20 nm were grown on three substrates (Al2O3, SiO2, and WCN) under the above ALD conditions using various supercycles depending on the Ti / Ru cycle ratio, as shown in Table 1 below.
[0088] [Table 1]
[0089] Thus, for example, RuTiN films with a Ti / Ru cycling ratio of 0.1 were grown on Al2O3, SiO2, and WCN, etc. The average growth rates of RuTiN films ("as-deposited") formed on the three substrates with the above Ti / Ru cycling ratios are shown in Figure 1A.
[0090] The RuTiN films formed as described above were also post-deposition annealed at 400 °C in the presence of argon. In other words, annealing was performed after the last super cycle was completed. The average growth rates of RuTiN films formed on the three substrates with the Ti / Ru cycle ratios mentioned above are shown in Figure 1B. Figure 1C compares the growth rates of RuTiN films grown on SiO2 ("as-deposited") with those of annealed RuTiN films grown on SiO2, showing the densification of the films upon annealing. A steady-state growth rate was reached for Ti / Ru cycle ratios of 0.33 and above.
[0091] [Example 2] Resistivity: Dependence on Ti / Ru cycle ratio and effect of annealing The resistivity of 13-20 nm thick RuTiN films grown on three substrates (Al2O3, SiO2, and WCN) under the above ALD conditions was measured using different supercycles depending on the Ti / Ru cycle ratio, as shown in Table 1. The resistivity was also measured for annealed RuTiN films formed as described above.
[0092] Figure 2A compares the resistivity of RuTiN films grown on Al2O3 ("as-deposited") with annealed RuTiN films grown on Al2O3. Figure 2B compares the resistivity of RuTiN films grown on SiO2 ("as-deposited") with annealed RuTiN films grown on SiO2. Figure 2C compares the resistivity of RuTiN films grown on WCN ("as-deposited") with annealed RuTiN films grown on WCN. The resistivity increased with increasing Ti / Ru cycling ratio, and annealing reduced the resistivity.
[0093] [Example 3] XPS analysis of thick RuTiN film on SiO2 XPS analysis was performed on a RuTiN film formed on SiO2 with a Ti / Ru cycle ratio of 1:2 (0.5). As a result, as shown in Figure 3A, the presence of Ru, Ti, and N in the film was confirmed, as well as the presence of oxygen due to exposure to the atmosphere.
[0094] Example 4: Resistivity of thin vs. thick RuTiN films RuTiN films with thicknesses between 13 and 20 nm ("thick films") were grown on three substrates (Al2O3, SiO2, and WCN) under the ALD conditions described above using different supercycles depending on the Ti / Ru cycle ratio as shown in Table 1. RuTiN films with thicknesses between 2 and 5 nm ("thin films") were grown on two substrates (Al2O3 and SiO2) under the ALD conditions described above using different supercycles depending on the Ti / Ru cycle ratio as shown in Table 2 below.
[0095] [Table 2]
[0096] The resistivity of the thick and thin films was measured. Figure 4A shows the change in resistivity of the as-deposited thick films with Ti / Ru cycle ratios in Table 1. Figure 4B shows the change in resistivity of the as-deposited thin films with Ti / Ru cycle ratios in Table 2. The results show that both thick and thin RuTiN films have similar resistivity trends with Ti / Ru cycle ratios on SiO2, but the films on Al2O3 need to be thicker to be conductive.
[0097] Example 5: Resistivity of thin vs. thick RuTiN films after annealing The thick and thin films of Example 4 were post-deposition annealed at 400° C. in the presence of argon as described above. The resistivity of the annealed thick films and annealed thin films was measured. FIG. 5A shows the change in resistivity of the annealed thick films with Ti / Ru cycle ratios from Table 1. FIG. 5B shows the change in resistivity of the annealed thin films with Ti / Ru cycle ratios from Table 2.
[0098] Example 6: Comparison of sheet resistance of various liner materials The sheet resistance of various liner materials on 100 nm thermal SiO2 was measured, as shown in Table 3.
[0099] [Table 3]
[0100] The as-deposited RuTiN liner material was formed under the ALD conditions listed above with a Ti / Ru cycling ratio of 1:2 (0.5). The annealed RuTiN liner material was formed under the ALD conditions listed above with a Ti / Ru cycling ratio of 1:2 (0.5) and post-deposition annealed at 400 °C in argon as described above. Both the as-deposited and annealed RuTiN liner materials had lower sheet resistance than TiN.
[0101] [Example 7] Roughness of RuTiN films on various substrates Roughness was determined for annealed RuTiN films formed on SiO2 under the ALD conditions described above with Ti / Ru cycle ratios as shown below in Table 4, and annealed as described above. Unless otherwise stated, roughness was measured by atomic force microscopy (AFM).
[0102] [Table 4]
[0103] SEM images of the films in Table 4 are shown in Figures 6A to 6E.
[0104] Roughness was determined for annealed RuTiN films formed on 4 nm Al2O3 / 100 nm SiO2 substrates ("Al2O3 substrate") and 25 nm Al2O3 / pure SiO2 substrates ("thick Al2O3 substrate" or "Al2O3_thick on Si") under the ALD conditions described above with Ti / Ru cycle ratios as shown below in Table 5, and annealed as described above. Unless otherwise stated, roughness was measured by atomic force microscopy (AFM).
[0105] [Table 5]
[0106] SEM images of the films in Table 5 are shown in Figures 7A-7D. Figure 7E is a graphical representation of AFM roughness (nm) versus Ti / Ru cycle ratio for the annealed films formed in Tables 4 and 5 and RuTiN films formed on TiN_OEM substrates under the ALD conditions described above.
[0107] [Example 8] Comparison of roughness between a Ru film formed on a RuTiN film and a Ru film formed directly on a substrate without a liner Roughness was determined for Ru films formed directly on SiO2 substrates, and for Ru films formed on RuTiN film liners on SiO2 or Al2O3 / 100 nm SiO2 ("Al2O3 / SiO2") under the ALD conditions described above with Ti / Ru cycle ratios as shown in Table 6 below. Ru films were formed using 55 ruthenium cycles on the RuTiN liner and 40 ruthenium cycles without a liner on the substrate as described above. Unless otherwise stated, roughness was measured by atomic force microscopy (AFM).
[0108] [Table 6]
[0109] SEM images of the films in Table 6 are shown in Figures 8A-8E.
[0110] [Example 9] Comparison of roughness of Ru films formed on various liners Ru films were formed by ALD on the following liners on SiO2: RuTiN, TiN (TiN deposited on 100 nm SiO2), TiN_OEM, and WCN. Ruthenium films can include delivering a first ruthenium precursor, a second nitrogen-containing co-reactant, and a purge gas to a substrate. Ru films were formed using 55 ruthenium cycles on the RuTiN liner and 40 ruthenium cycles on the substrate without a liner, as described above.
[0111] The RuTiN liner was formed by the ALD method described above with a Ti / Ru cycle ratio of 1:2 (0.5). We also formed the Ru film directly on the SiO2 without using a liner. The roughness comparison of the formed Ru films is shown in Figure 9A.
[0112] Ru films were also formed by ALD on the following liners on Al2O3 / 100nm SiO2: RuTiN, TiN, TiN on Al2O3 / Si (TiN on Al2O3 on Si substrate with pure oxide). The RuTiN liner was formed by the above ALD method with Ti / Ru cycle ratio of 1:2 (0.5). Ru films were also formed directly on 4nm Al2O3 / 100nm SiO2 without using a liner. A comparison of the roughness of the formed Ru films is shown in Figure 9B.
[0113] Example 10: Dependence of roughness on liner thickness Roughness was determined for annealed RuTiN films formed on 100 nm SiO or 4 nm Al2O3 / 100 nm SiO2 with the ALD conditions listed above and with Ti / Ru cycle ratios as shown in Table 7 below and annealed as described above.
[0114] [Table 7]
[0115] SEM images of the films in Table 7 are shown in Figures 10A-10E. Figure 10F shows a graph of roughness versus film thickness for the films in Table 7.
[0116] [Example 11] Formation of membrane within pores A 3 nm thick RuTiN liner was deposited on the hole structure by the above ALD method with a Ti / Ru cycle ratio of 1:2 (0.5) and 10 super cycles. A 6.5 nm thick Ru film was then deposited on top of the RuTiN liner with 55 ruthenium cycles. Figures 11A and 11B are cross-sectional SEM images of the hole structure with a Ru film coated on top of the RuTiN liner.
[0117] All publications, patent applications, issued patents, and other documents mentioned herein are incorporated by reference herein as if each individual publication, patent application, issued patent, or other document was specifically and individually indicated to be incorporated by reference in its entirety. Definitions contained in sentences incorporated by reference are excluded to the extent that they conflict with definitions in this disclosure.
[0118] The terms "comprise", "comprises" and "comprising" are to be interpreted inclusively rather than exclusively. [Brief description of the drawings]
[0119] [Figure 1A] FIG. 1 is a graphical representation of the growth rate (nm / cycle) of as-deposited ruthenium-titanium nitride (RuTiN) films versus Ti / Ru cycle ratio for RuTiN films grown on three substrates (Al2O3, SiO2, and WCN) according to Example 1. [Figure 1B] 1 is a graphical representation of the growth rate (nm / cycle) of annealed RuTiN films versus Ti / Ru cycle ratio for annealed RuTiN films grown on three substrates (Al 2 O 3 , SiO 2 , and WCN) according to Example 1. 1 [Figure 1C] FIG. 1C is a graphical representation comparing growth rate (nm / cycle) versus Ti / Ru cycle ratio for as-deposited RuTiN films grown on SiO2 and annealed RuTiN films grown on SiO2 from FIGS. 1A and 1B. [Figure 2A] 1 is a graphical representation comparing resistivity (μΩcm) versus Ti / Ru cycling ratio for as-deposited RuTiN films grown on Al2O3 ("as-deposited") and annealed RuTiN films grown on Al2O3. [Figure 2B]1 is a graphical representation comparing resistivity (μΩcm) versus Ti / Ru cycling ratio for as-deposited RuTiN films grown on SiO2 ("as-deposited") and annealed RuTiN films grown on SiO2. [Figure 2C] 1 is a graphical representation comparing resistivity (μΩcm) versus Ti / Ru cycling ratio for as-deposited RuTiN films grown on WCN ("as-deposited") and annealed RuTiN films grown on WCN. [Figure 3A] 1 is a graphical representation of the XPS depth profile of annealed RuTiN films formed on SiO2 with a Ti / Ru cycling ratio of 1:2. [Figure 4A] FIG. 11 is a graphical representation comparing resistivity (μΩcm) versus Ti / Ru cycling ratio for as-deposited thick RuTiN films (13-20 nm) grown on Al2O3, SiO2, and WCN according to Example 4. [Figure 4B] FIG. 11 is a graphical representation comparing resistivity (μΩcm) versus Ti / Ru cycling ratio for as-deposited thin RuTiN films (2-5 nm) grown on Al2O3, SiO2, and WCN according to Example 4. [Figure 5A] FIG. 11 is a graphical representation comparing resistivity (μΩcm) versus Ti / Ru cycling ratio for annealed thick RuTiN films (13-20 nm) grown on Al2O3, SiO2, and WCN according to Example 5. [Figure 5B] 13 is a graphical representation comparing resistivity (μΩcm) versus Ti / Ru cycle ratio for annealed thin RuTiN films (2-5 nm) grown on Al 2 O 3 , SiO 2 , and WCN according to Example 5. [Figure 6A] FIG. 1 is a scanning electron microscope (SEM) image of the surface of an annealed RuTiN film formed on SiO2 with a Ti / Ru cycle ratio of 1:4. [Figure 6B] FIG. 1 is a scanning electron microscope (SEM) image of the surface of an annealed RuTiN film formed on SiO2 with a Ti / Ru cycle ratio of 1:3. [Figure 6C] FIG. 1 is a scanning electron microscope (SEM) image of the surface of an annealed RuTiN film formed on SiO2 with a Ti / Ru cycle ratio of 1:2. [Figure 6D] FIG. 1 is a scanning electron microscope (SEM) image of the surface of an annealed RuTiN film formed on SiO2 with a Ti / Ru cycle ratio of 2:3. [Figure 6E] FIG. 1 is a scanning electron microscope (SEM) image of the surface of an annealed RuTiN film formed on SiO2 with a Ti / Ru cycle ratio of 1:1. [Figure 7A] FIG. 13 is an SEM image of the surface of an annealed RuTiN film formed on 4 nm Al2O3 / 100 nm SiO2 with a Ti / Ru cycle ratio of 1:3. [Figure 7B] FIG. 11 is an SEM image of the surface of an annealed RuTiN film formed on 4 nm Al2O3 / 100 nm SiO2 with a Ti / Ru cycle ratio of 1:2. [Figure 7C] FIG. 11 is an SEM image of the surface of an annealed RuTiN film formed on 4 nm Al2O3 / 100 nm SiO2 with a Ti / Ru cycle ratio of 1:1. [Figure 7D] SEM images of the surface of annealed RuTiN films with a Ti / Ru cycle ratio of 1:1 on 25 nm Al2O3 / pure SiO2 (denoted as "thick Al2O3" or "Al2O3_thick on Si"). [Figure 7E] 1 is a graphical representation of AFM roughness (nm) versus Ti / Ru cycle ratio for annealed films formed on various substrates. [Figure 8A] SEM images of the surfaces of as-deposited Ru films formed directly on 100 nm SiO2 substrates (no liner) and Ru films formed in place on as-deposited RuTiN film liners on 100 nm SiO2 or 4 nm Al2O3 / 100 nm SiO2. [Figure 8B]SEM images of the surfaces of as-deposited Ru films formed directly on 100 nm SiO2 substrates (no liner) and Ru films formed in place on as-deposited RuTiN film liners on 100 nm SiO2 or 4 nm Al2O3 / 100 nm SiO2. [Figure 8C] SEM images of the surfaces of as-deposited Ru films formed directly on 100 nm SiO2 substrates (no liner) and Ru films formed in place on as-deposited RuTiN film liners on 100 nm SiO2 or 4 nm Al2O3 / 100 nm SiO2. [Figure 8D] SEM images of the surfaces of as-deposited Ru films formed directly on 100 nm SiO2 substrates (no liner) and Ru films formed in place on as-deposited RuTiN film liners on 100 nm SiO2 or 4 nm Al2O3 / 100 nm SiO2. [Figure 8E] SEM images of the surfaces of as-deposited Ru films formed directly on 100 nm SiO2 substrates (no liner) and Ru films formed in place on as-deposited RuTiN film liners on 100 nm SiO2 or 4 nm Al2O3 / 100 nm SiO2. [Figure 9A] FIG. 1 is a graphical representation of AFM roughness (nm) versus Ru thickness (nm) measured by X-ray fluorescence (XRF) for Ru films formed by ALD on liners (RuTiN, TiN, TiN_OEM, and WCN) on 100 nm SiO2. [Figure 9B] FIG. 1 is a graphical representation of AFM roughness (nm) versus Ru thickness (nm) measured by X-ray fluorescence (XRF) for Ru films formed by ALD on liners (RuTiN, TiN, and TiN on 25 nm AlO / Si with pure SiO (AlO / Si)) on 4 nm AlO / 100 nm SiO. [Figure 10A] SEM images of the surface of RuTiN films formed on 100 nm SiO2 or 4 nm Al2O3 / 100 nm SiO2. [Figure 10B]SEM images of the surface of RuTiN films formed on 100 nm SiO2 or 4 nm Al2O3 / 100 nm SiO2. [Figure 10C] SEM images of the surface of RuTiN films formed on 100 nm SiO2 or 4 nm Al2O3 / 100 nm SiO2. [Figure 10D] SEM images of the surface of RuTiN films formed on 100 nm SiO2 or 4 nm Al2O3 / 100 nm SiO2. [Figure 10E] SEM images of the surface of RuTiN films formed on 100 nm SiO2 or 4 nm Al2O3 / 100 nm SiO2. [Figure 10F] 1 is a graphical representation of AFM roughness (nm) versus estimated RuTiN liner thickness (nm) for annealed RuTiN films formed on 100 nm SiO2 or 4 nm Al2O3 / 100 nm SiO2. [Figure 11A] Cross-sectional SEM image of a hole structure coated with 6.5 nm of Ru on top of a 3 nm in-place RuTiN liner (1:2 cycle ratio) deposited at 225°C. [Figure 11B] Cross-sectional SEM image of a hole structure coated with 6.5 nm of Ru on top of a 3 nm in-place RuTiN liner (1:2 cycle ratio) deposited at 225°C.
Claims
1. 1. A method for forming a ruthenium-containing film on a substrate, comprising: A first step of forming a first film on a surface of the substrate, comprising: (i) delivering a titanium precursor and a first nitrogen-containing co-reactant to the substrate; and (ii) delivering a first ruthenium precursor and a second nitrogen-containing co-reactant to the substrate to form a first film; a second step of forming the ruthenium-containing film on at least a portion of the first film, the second step comprising delivering a second ruthenium precursor and a third co-reactant to the substrate and / or the first film; Including, and / or the first film has an average roughness of about 0.65 nm or less as measured by AFM; and The method wherein the ruthenium-containing film has an average roughness of about 1.6 nm or less as measured by AFM.
2. carrying out the first step, the second step, or both steps at a temperature of about 300° C. or less; and / or The method of claim 1 , wherein the first step, the second step, or both steps are carried out in an inert atmosphere.
3. The method of claim 1, wherein the first film comprises ruthenium-titanium nitride.
4. 2. The method of claim 1 , wherein the structure of the titanium precursor corresponds to Formula I: [R 1 R 2 N] 4 Tì (Form I) In the formula, R 1 and R 2 are each independently 1 ~C 6 It is an alkyl.
5. the titanium precursor is selected from the group consisting of tetrakis(dimethylamido)titanium, tetrakis(ethylmethylamido)titanium, and tetrakis(diethylamido)titanium; and / or The first ruthenium precursor has a structure of (η 4 -2,3-dimethylbuta-1,3-diene)tricarbonylruthenium ((DMBD)Ru(CO) 3 ), (η 4 -buta-1,3-diene)tricarbonylruthenium ((BD)Ru(CO) 3 ), (1,3-cyclohexadienyl)tricarbonyl ruthenium (((CHD)Ru(CO) 3 ), (η 4 -2-methylbuta-1,3-diene)tricarbonyl ruthenium, or triruthenium dodecacarbonyl Ru 3 (CO) 12 and the second ruthenium precursor comprises (η 4 -2,3-dimethylbuta-1,3-diene)tricarbonylruthenium ((DMBD)Ru(CO) 3 ), (η 4 -buta-1,3-diene)tricarbonylruthenium ((BD)Ru(CO) 3 ), (1,3-cyclohexadienyl)tricarbonyl ruthenium (((CHD)Ru(CO) 3 ), (η 4 -2-methylbuta-1,3-diene)tricarbonyl ruthenium, triruthenium dodecacarbonyl Ru 3 (CO) 12 , (ethylbenzyl)(1-ethyl-1,4-cyclohexadienyl)ruthenium (Ru(EtBz)(EtCHD)), bis(ethylcyclopentadienylruthenium (Ru(EtCp) 2 ), (cyclopentadienyl)(ethyl)biscarbonylruthenium (Cp(Et)Ru(CO) 2 ), or (N,N'-diisopropylacetamidinato)biscarbonylruthenium ((amidinato)Ru(CO) 2 ) and / or The first nitrogen-containing co-reactant and the second nitrogen-containing co-reactant are each independently selected from the group consisting of NH 3 , alkylamines, hydrazines, alkylhydrazines, and combinations thereof, and the third co-reactant is selected from the group consisting of hydrogen, hydrogen plasma, nitrogen plasma, ammonia plasma, oxygen, air, water, borane, silane, ozone, NH 3 2. The method of claim 1, wherein the organic solvent is selected from the group consisting of alkylamines, hydrazines, alkylhydrazines, and combinations thereof.
6. 10. The method of claim 1 , wherein the first step comprises one or more supercycles comprising the following cycles: a titanium cycle comprising delivering the titanium precursor, the first nitrogen-containing co-reactant, and a purge gas to a substrate; and A ruthenium cycle comprising delivering the first ruthenium precursor, the second nitrogen-containing co-reactant, and a purge gas to a substrate.
7. 7. The method of claim 6, wherein the ratio of said titanium cycle to said ruthenium cycle is from about 1:1 to about 2:
12.
8. 2. The method of claim 1, wherein the second step comprises an additional ruthenium cycle comprising delivering the second ruthenium precursor, the third co-reactant, and a purge gas to the substrate.
9. The method of claim 1, wherein the first film has a Ti:Ru concentration ratio of about 1:10 to about 10:
1.
10. The method of claim 1 , wherein the first film has a thickness of about 1 nm to about 5 nm and a resistivity of about 20 μΩcm to about 3000 μΩcm.
11. annealing the first film in an inert gas at a temperature of about 400° C. or greater; and / or 10. The method of claim 1, further comprising annealing the ruthenium-containing film in an inert gas at a temperature of about 400° C. or greater.
12. the first step and the second step are independently chemical vapor deposition or atomic layer deposition; and / or The method of claim 1 , wherein the first step, the second step, or a combination thereof further comprises using a plasma.
13. a first film deposited on a surface of a substrate, the first film comprising a first reaction product of a titanium precursor and a first nitrogen-containing co-reactant and a second reaction product of a first ruthenium precursor and a second nitrogen-containing co-reactant; and a ruthenium-containing film deposited on at least a portion of the first film, the ruthenium-containing film comprising a third reaction product of a second ruthenium precursor and a third co-reactant; Including, A ruthenium-containing film, wherein the average roughness of the ruthenium-containing film is about 1.6 nm or less as measured by AFM.
14. the first film comprises a first layer deposited on a surface of the substrate, the first layer comprising the first reaction product; and / or The ruthenium-containing film of claim 13, wherein the first film comprises ruthenium-titanium nitride.
15. the first film further comprises a second layer deposited on at least a portion of the first layer, the second layer comprising the second reaction product; and / or 15. The ruthenium-containing film of claim 14, wherein the first layer further comprises ruthenium as a dopant.
16. 14. The ruthenium-containing film of claim 13, wherein the structure of the titanium precursor corresponds to Formula I: [R 1 R 2 N] 4 Tì (Form I) In the formula, R 1 and R 2 are each independently 1 ~C 6 It is an alkyl.
17. the titanium precursor is selected from the group consisting of tetrakis(dimethylamido)titanium, tetrakis(ethylmethylamido)titanium, and tetrakis(diethylamido)titanium; and / or The first ruthenium precursor has a structure of (η 4 -2,3-dimethylbuta-1,3-diene)tricarbonylruthenium ((DMBD)Ru(CO) 3 ), (η 4 -buta-1,3-diene)tricarbonylruthenium ((BD)Ru(CO) 3 ), (1,3-cyclohexadienyl)tricarbonyl ruthenium (((CHD)Ru(CO) 3 ), (η 4 -2-methylbuta-1,3-diene)tricarbonyl ruthenium, or triruthenium dodecacarbonyl Ru 3 (CO) 12 and the second ruthenium precursor comprises (η 4 -2,3-dimethylbuta-1,3-diene)tricarbonylruthenium ((DMBD)Ru(CO) 3 ), (η 4 -buta-1,3-diene)tricarbonylruthenium ((BD)Ru(CO) 3 ), (1,3-cyclohexadienyl)tricarbonyl ruthenium (((CHD)Ru(CO) 3 ), (η 4 -2-methylbuta-1,3-diene)tricarbonyl ruthenium, triruthenium dodecacarbonyl Ru 3 (CO) 12 , (ethylbenzyl)(1-ethyl-1,4-cyclohexadienyl)ruthenium (Ru(EtBz)(EtCHD)), bis(ethylcyclopentadienylruthenium (Ru(EtCp) 2 ), (cyclopentadienyl)(ethyl)biscarbonylruthenium (Cp(Et)Ru(CO) 2 ), or (N,N'-diisopropylacetamidinato)biscarbonylruthenium ((amidinato)Ru(CO) 2 ) and / or The first nitrogen-containing co-reactant and the second nitrogen-containing co-reactant are each independently selected from the group consisting of NH 3 , H 2 , hydrazine, alkylhydrazine, and combinations thereof, and the third co-reactant is independently selected from the group consisting of hydrogen, hydrogen plasma, nitrogen plasma, ammonia plasma, oxygen, air, water, borane, silane, ozone, NH 3 , H 2 14. The ruthenium-containing film of claim 13, wherein the ruthenium-containing compound is selected from the group consisting of hydrazine, alkylhydrazine, and combinations thereof.
18. 14. The ruthenium-containing film of claim 13, wherein the first film has one or more of the following: (i) a Ti:Ru concentration ratio of about 1:10 to about 10:1; (ii) an average roughness as measured by AFM of about 0.65 nm or less; and (iii) a thickness of about 1 nm to about 5 nm and a resistivity of about 20 μΩcm to about 3000 μΩcm.
Citation Information
Patent Citations
Interconnect structures with a metal nitride diffusion barrier containing ruthenium and method of forming
US20080206982A1
Methods of vapor deposition of ruthenium using an oxygen-free co-reactant
WO2019154945A1